2023
DOI: 10.33971/bjes.23.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Strength Characteristics of Clay Soil Reinforced with Natural Fibers

Abstract: The trend of using natural fibers in geotechnical engineering has become of great interest to improve weak soils due to some of its advantages such as local availability, environmental friendliness, and lower cost. In this study, a set of unconfined compression strength and direct shear tests were conducted to evaluate the performance of Al-Nasiriya clayey soil reinforced with natural fibers. Three different types of natural fibers were investigated as sustainable ones, including wheat straw fiber and palm fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In the realm of earth construction, there is a trend towards characterizing fibers [25] or waste materials [26] for their potential as new construction materials. The addition of fibers or industrial waste has been shown to effectively enhance the properties of earth blocks [27] and even geopolymer composites [2].…”
mentioning
confidence: 99%
“…In the realm of earth construction, there is a trend towards characterizing fibers [25] or waste materials [26] for their potential as new construction materials. The addition of fibers or industrial waste has been shown to effectively enhance the properties of earth blocks [27] and even geopolymer composites [2].…”
mentioning
confidence: 99%